2015
DOI: 10.1016/j.marpol.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic ocean management: Defining and conceptualizing real-time management of the ocean

Abstract: a b s t r a c tMost spatial marine management techniques (e.g., marine protected areas) draw stationary boundaries around often mobile marine features, animals, or resource users. While these approaches can work for relatively stationary marine resources, to be most effective marine management must be as fluid in space and time as the resources and users we aim to manage. Instead, a shift towards dynamic ocean management is suggested, defined as management that rapidly changes in space and time in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
289
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 376 publications
(291 citation statements)
references
References 58 publications
(86 reference statements)
2
289
0
Order By: Relevance
“…Although these tools allow for operational implementation of DOM, there is a larger question of how DOM fits within current fisheries management regimes. Previous studies have shown that DOM does not seek to supplant existing adaptive management processes but falls within the implementation component of that framework (7,8). For example, move-on rules as they are currently implemented in numerous fisheries do not occur at a predetermined time or location and do not require management council review for each application of the measure (5, 10); rather, the distance which fishermen must move following a bycatch event is determined during the council review process and the move-on rule is applied in near real time on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although these tools allow for operational implementation of DOM, there is a larger question of how DOM fits within current fisheries management regimes. Previous studies have shown that DOM does not seek to supplant existing adaptive management processes but falls within the implementation component of that framework (7,8). For example, move-on rules as they are currently implemented in numerous fisheries do not occur at a predetermined time or location and do not require management council review for each application of the measure (5, 10); rather, the distance which fishermen must move following a bycatch event is determined during the council review process and the move-on rule is applied in near real time on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing static and dynamic measures are lacking despite the potential to increase efficiency through the use of dynamic measures to align the scales of resource variability, resource use, and resource management (7,8). In a precursor to the recent work on dynamic management, Grantham et al (42) looked at the efficiency of closures to reduce bycatch by examining permanent full-fishery closures, seasonal full-fishery closures, and a series of temporary (monthly) time-area closures.…”
Section: Evaluation Of Static Vs Dynamic Management Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellites are also revolutionising the management of offshore fi sheries. Near real-time measures of ocean primary production [2] are allowing fi sheries managers to restrict vessel access dynamically, rather than permanently closing larger -and often unnecessarily large -areas as a means of controlling fi shing effort [3].…”
Section: Tooling Up To Understand the Oceansmentioning
confidence: 99%